THE EFFECT OF SERVICE PERFORMANCE, MEANS, TASK SUITABILITY AND SELF-EFFICIENCY ON IMPROVING THE QUALITY OF LEARNING AT TAKHOSSUS INSTITUTION DINY BAHRUL ULUM - Mahasini, Zadana Bil (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Every individual has certainly hopes or expectations of things or the environment in which they stand. Likewise with students who place themselves in Islamic boarding schools, of course they want comfort and tranquility in the learning process so that it is easy to absorb knowledge. The performance provided by an educational institution will be a measure of comfort in the learning process both in terms of services, facilities, suitability of tasks given by the teacher and selfefficacy. Some of these things are expected to be embedded in the performance of an institution so that it can improve the quality of existing learning. Because the more comfortable the learning process that students go through, the more quality it will produce. The results of the study show that the four performance variables have a positive effect on the learning quality of students at the Takhossus Diny Bahrul Ulum Institute